2004
DOI: 10.1111/j.1365-3180.2004.00389.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial stability of Avena sterilis ssp. ludoviciana populations under annual applications of low rates of imazamethabenz

Abstract: Summary Long‐term experiments were conducted in two winter barley fields in central Spain to determine the spatial stability of Avena sterilis ssp. ludoviciana populations under annual applications of low rates of imazamethabenz herbicide. Weed density was sampled every year (over 5 years in the first field and over 3 years in the second) on the same grid locations prior to herbicide application. Although weed patches were stable in their location, weed density decreased in most of the years. In the first fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
44
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 23 publications
2
44
0
Order By: Relevance
“…The results obtained in this study have several important implications for SSWM of S. halepense. Previous studies have shown that the economic feasibility of using SSWM systems is conditioned by the frequency of re-mapping (Van Wychen et al, 2002;Barroso et al, 2004). Our results indicate that S. halepense patches are generally very compact and they expand slowly in a highly predictable way (in the same direction of field traffic).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The results obtained in this study have several important implications for SSWM of S. halepense. Previous studies have shown that the economic feasibility of using SSWM systems is conditioned by the frequency of re-mapping (Van Wychen et al, 2002;Barroso et al, 2004). Our results indicate that S. halepense patches are generally very compact and they expand slowly in a highly predictable way (in the same direction of field traffic).…”
Section: Discussionmentioning
confidence: 57%
“…Previous studies have shown that the economic feasibility of using SSWM systems is conditioned by the frequency of re‐mapping (Van Wychen et al. , 2002; Barroso et al. , 2004).…”
Section: Discussionmentioning
confidence: 99%
“…This straightforward and easy to understand method requires that the existence and spatial delineation of the patches is determined first. The method of Syrjala (1996), applied to weeds by Barroso et al. (2004), can be used to test whether patterns observed in 2 years are similar or not.…”
Section: Discussionmentioning
confidence: 99%
“…This straightforward and easy to understand method requires that the existence and spatial delineation of the patches is determined first. The method of Syrjala (1996), applied to weeds by Barroso et al (2004), can be used to test whether patterns observed in 2 years are similar or not. As this method provides only a yes ⁄ no answer, further exploration of the type of similarity or dissimilarity would seem useful to characterise the data more fully after this test has produced an outcome.…”
mentioning
confidence: 99%
“…Other approaches have used colour indices to distinguish vegetation material from background [9], Unlike the above approach our method tries to identify and classify a special weed seed, the avena sterilis ssp. Ludoviciana, which is one of the most widely distributed and abundant weed of cereals in Spain and other regions with Mediterranean climate and causes substantial losses in these crops [10,11]. The main problem concerning its classification is that during the herbicide treatment its colour and texture are undistinguishable with respect to the seed cereal (barley).…”
Section: Introductionmentioning
confidence: 99%